Rofa dan Randai: A Culturally-Based Children's Storybook with Digital Integration - Nana Fauzana Azima; Salmaini Safitri Syami; Arif Algifari; Nelfira Anjani; Sarah Ibrahim (Universitas Pendidikan Ganesha, 2025)
Children's cultural awareness may diminish if not introduced early, leading to a lack of appreciation for local traditions. This study addresses this issue by developing a culturally enriched storybook to enhance elementary school students' understanding of Minangkabau culture. The research aims to develop and evaluate an Indonesian-language children's storybook that integrates digital reading media with video access to improve students' cultural awareness and literacy skills. This study employs the Research and Development (R&D) method by Borg and Gall, consisting of preliminary analysis, storybook development, expert validation, limited and broader trials, experimental testing, and dissemination. The research was conducted at SDN 11 Bukit Apit Puhun, Bukittinggi, involving 29 fourth-grade students as subjects. Data collection included expert validation, student and teacher assessments, and effectiveness testing using a normal gain score. The storybook Rofa dan Randai received high validity ratings in terms of graphics, linguistics, and content, with minor revisions suggested. Practicality tests indicate that educators and students found the storybook highly usable. Effectiveness analysis showed moderate improvements in students' cultural understanding and literacy skills. Students demonstrated better comprehension of cultural messages, enhanced reading skills, and improved ability to identify main ideas within the stories. These findings confirm that the developed storybook is a valuable tool for fostering both cultural awareness and literacy in young learners.